The Effect of Internet Use on Physics Learning Outcomes in Terms of Student Learning Styles - Perdy KARURU; Yulianti PARA'PAK (International Journal of Environmental, Sustainability, and Social Science, 2023)
This study aims to determine the influence of internet use on physics learning outcomes in terms of student learning styles (including visual learning styles, auditorial learning styles, and kinesthetic learning styles). This study was conducted on 314 junior high school students in Tana Toraja Regency. Data collection techniques in the form of questionnaires and documentation. The data from the study were analyzed using the SPSS version 22 computer application. The results showed: (1) there was a positive and significant influence of internet use on the learning outcomes of physics students at Tana Toraja Regency Junior High School; (2) there is no influence of internet use on physics learning outcomes in terms of the learning styles of junior high school students in Tana Toraja Regency; and (3) the learning style that has the highest influence on the physics learning outcomes of junior high school students in Tana Toraja Regency is the visual learning style with a total percentage of 33.8 and the total influence of internet use on learning outcomes in terms of the visual learning style of students of 82.9%.